2019
DOI: 10.1002/naaq.10091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Dietary Levels of Cottonseed Meal and Rapeseed Meal on Growth Performance, Muscle Texture, and Expression of Muscle‐Related Genes in Grass Carp

Abstract: A 10‐week feeding experiment was conducted to estimate the effects of rapeseed meal (RSM) and cottonseed meal (CSM) as a replacement for equal proportions of fish meal and soybean meal for Grass Carp Ctenopharyngodon idella. Two isonitrogenous and isoenergetic diets were formulated; a basic commercial formula was fed to the control (CT) group, while the RSM and CSM diet was fed to the experimental (ET) group. The results showed that the survival rates were 98% (CT group) and 99% (ET group), which were not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
(35 reference statements)
3
9
0
Order By: Relevance
“…These results supported our current findings. Moreover, (Hu et al, 2019) reported that the dietary CSM and rapeseed meal inclusion in grass carp lead to increase muscle hardness, gumminess and chewiness but do not affect cohesiveness and springiness due to anti‐nutritional factors in CSM and rapeseed meal that affect the structure of muscle fibres, which partially agrees with our findings. Likewise, Abouel Azm et al, (2021) confirmed that DDGS dietary inclusion caused a softer cooked flesh texture of grass carp.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results supported our current findings. Moreover, (Hu et al, 2019) reported that the dietary CSM and rapeseed meal inclusion in grass carp lead to increase muscle hardness, gumminess and chewiness but do not affect cohesiveness and springiness due to anti‐nutritional factors in CSM and rapeseed meal that affect the structure of muscle fibres, which partially agrees with our findings. Likewise, Abouel Azm et al, (2021) confirmed that DDGS dietary inclusion caused a softer cooked flesh texture of grass carp.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in gene expression of MRFs and mstn1 in the control group reflects the higher potential for muscle regeneration in this group, which indicates that fish body produces more muscle cells to compensate the growth depression caused by the anti‐nutritional factors such as gossypol in CSM. This could be confirmed by previous studies (Aksnes et al, 1986; Hu et al, 2019; Ulloa et al, 2013; Xu et al, 2019; Zhao et al, 2018), all of which suggested that muscle regeneration occurred in growth‐restricted fish. Upregulation of mstn gene expression in the control group compared with DDGS containing groups indicated that mstn may prevent the hypertrophy of fish muscle cells rather than differentiation, that confirmed the results by Lee and McPherron (2001).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In contrast, the upregulation of myog and myhc expression in the native DDGS-containing groups reflects the better capacity of muscle regeneration in these groups, which might suggest the compensatory process for the growth depression caused by higher crude fiber in the native DDGS. These results may explain why the hardness of muscle increased significantly in the native DDGS groups, which agrees with the results reported by Hu et al ( 53 ). Moreover, our results are consistent with that the difference in body weight between treatments was contributed to the modulation of myog gene expression in male zebrafish fed a PP diet with low growth vs. high growth, which indicated that myog expression was more active, due to possible muscle renewal, in fish with a slower growth rate than those with a faster growth rate ( 54 ).…”
Section: Discussionsupporting
confidence: 93%
“…Cottonseed meal (CSM) is an important plant protein source. It is widely used in feeds of different fish species, such as juvenile black sea bream ( Acanthopagrus schlegelii ) (Sun et al, 2015), juvenile black carp ( Mylopharyngodon piceus ) (Hu et al, 2015), juvenile ussuri catfish ( Pseudobagrus ussuriensis ) (Bu et al, 2017), grass carp (Hu et al, 2019), juvenile blunt snout bream ( Megalobrama amblycephala ) (Yuan et al, 2019), silver sillago ( Sillago sihama Forsskal) (Liu, Dong, et al, 2020), largemouth bass ( Micropterus salmoides ) (Ni et al, 2021) and others. However, the free gossypol contained in cottonseed meal is toxic to fish, limiting its addition in fish feed.…”
Section: Introductionmentioning
confidence: 99%